Assessment of the Nurse’s Role Regarding drug Administration of Cardiovascular Patients - Younis, Yousif; hussien, Ronak (Iraqi National Journal of Nursing Specialties, 2014)
Objectives: The aim of the study was, to assess the nurse's role regarding cardiovascular drugadministration in Erbil city.Methodology: A descriptive survey was conducted in Hawler teaching and Rizgari teaching Hospitals. Thenumber of samples is 50 nurses; the period of the study was started from 15th of November 2008 up tothe end of March 2009. A questionnaire was developed by investigators based on extensive review ofavailable studies and literatures. Data were collected through application of observational check listconsist of two part, part one was demographic sheet and part two about nurse’s responsibility regardingmedication administration which include (before, during, after drug administration). Data were analyzedthrough the application of descriptive statistical analysis such as (frequency, percentages and grand meanof scores).Results: Results showed that (72%) of nurses were within age group of (31-40) years, (66%) of themwere married, and (64%) of them were institute graduated. The study showed that nurses' practices wereinadequate with low grand mean of score in most items regarding assessment of patients before, duringand after drug administration.Recommendations: Increase nursing staff awareness about cardio vascular drug administration throughperforms training on cardiac medication administration, follow up nurses' practice during drugadministration and follow up the five rights of cardiac drug administration.